Sustainable and Repulpable Barrier Coatings for Fiber-Based Materials for Food Packaging: A Review - Kathuria, Ajay; Zhang, Shanju (Frontiers in Materials, 2022)
Due to inherent hydrophilic nature and porosity of the paper fibers, hydrophobic polymeric materials, waxes, and inorganic fillers have been widely utilized as coatings and filler respectively on a fiber-based substrate. Coatings also impart oxygen, aroma, and oil barrier properties desirable for food packaging applications. In addition, coatings improve the functional properties and characteristics of paper including reduced water absorbance, enhances surface finish, gloss finish, printability, readability, dimensional stability of the substrate and antimicrobial performance among others. Such functional properties are highly desirable for consumer packaging applications. However, such coatings may limit the repulpability, recyclability, biodegradability and compostability of paper and paperboard. In addition, the contamination of the substrate by product also limits the recyclability of the fiber-based substrates and the paper, paperboard or corrugate end up in the landfill sites. This review focuses on bioderived, biodegradable, compostable and functional organic, inorganic and hybrid hydrophobic coatings which promote the circular economy by improving the repulpability and/or reduce the carbon footprints.